(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article dwells upon nomination of an object, phenomenon and action based upon speaking activity. In modern linguistics the theory of nomination is not directly connected only to an object, phenomenon, and action, but also to the national conscience, national thought, and national world perception system. Nomination process in language structure is regarded as a result of speaking activity. Nomination function allows us to consider the general linguistic concept of an «action» as connected to the environment, background knowledge, and extralinguistic factors. Because nomination of an object, phenomenon, quality and action is connected to the world perception, development of thought and consciousness, national psychology and mentality. The fact that environment and phenomena around us are reflected on human consciousness through mental and tactile senses has been proved with the help of exact linguistic facts.